Knockdown of the C. elegans kinome identifies kinases required for normal protein homeostasis, mitochondrial network structure, and sarcomere structure in muscle - Lehmann, Susann; Bass, Joseph J.; Szewczyk, N.J. (BioMed Central, 2013)
Kinases are important signalling molecules for modulating cellular processes and major targets of drug discovery programs. However, functional information for roughly half the human kinome is lacking. We conducted three kinome wide, >90%, RNAi screens and epistasis testing of some identified kinases against known intramuscular signalling systems to increase the functional annotation of the C. elegans kinome and expand our understanding of kinome influence upon muscle protein degradation.